Novel effects of acute COVID‐19 on cardiac mechanical function: Two case studies. Issue 17 (27th August 2021) - Singh, Jyotpal; Bhagaloo, Lanishen; Sy, Eric; Lavoie, Andrea J.; Dehghani, Payam; Neary, Patrick
Abstract: The spread of the novel coronavirus 2019 (COVID‐19) has caused a global pandemic. The disease has spread rapidly, and research shows that COVID‐19 can induce long‐lasting cardiac damage. COVID‐19 can result in elevated cardiac biomarkers indicative of acute cardiac injury, and research utilizing echocardiography has shown that there is mechanical dysfunction in these patients as well, especially when observing the isovolumic, systolic, and diastolic portions of the cardiac cycle. The purpose of this study was to present two case studies on COVID‐19 positive patients who had their cardiac mechanical function assessed every day during the acute period to show that cardiac function in these patients was altered, and the damage occurring can change from day‐to‐day. Participant 1 showed compromised cardiac function in the systolic time, diastolic time, isovolumic time, and the calculated heart performance index (HPI), and these impairments were sustained even 23 days post‐symptom onset. Furthermore, Participant 1 showed prolonged systolic periods that lasted longer than the diastolic periods, indicative of elevated pulmonary artery pressure. Participant 2 showed decreases in systole and consequently, increases in HPI during the 3 days post‐symptom onset, and these changes returned to normal after day 4. These results showed that daily observation of cardiac function can provide detailed information about the overall mechanism by which cardiac dysfunction is occurring and that COVID‐19 can induce cardiac damage in unique patterns and thus can be studied on a case‐by‐case basis, day‐to‐day during infection. This could allow us to move toward more personalized cardiovascular medical treatment. Abstract : Daily assessments of mechanical cardiac function provides insights to impairments and potential mechanisms in cardiac function following COVID‐19. A young participant with no previous medical history showed altered cardiac function which varied from day to day, and this damage was sustained for up to 3 weeks, whereas an older participant showed acute cardiac damage which was sustained for 3 days before returning to normal.